Robust authenticated encryption scheme with multiple keys for ad hoc networks - Ajay Kakkar; Maninder Singh (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Data security in a computing dynamic infrastructure without explicit user intervention is tough to achieve. A robust authenticated encryption scheme with multiple keys for ad hoc networks has been proposed. Real time attacks has been monitored and coped up using re-encryption algorithm. The effectiveness of the work has been validated by extensive simulations on various combination in terms of S-Boxes, key and data length. The proposed work is a collaboration of optimal selection of S-Boxes, key and data lengths with evaluation of heat dissipation. The work has been carried out to develop an optimized efficient key management technique to reduce the time available for hackers. To verify the effectiveness of proposed algorithm, the results have been compared with K. Xue et al. (2013) , Li et al. (2011) and S. K. Sood et al.’s protocol (2011)